Strategi Lembaga Amil Zakat dalam Meningkatkan Partisipasi Generasi Muda - Amalia, Fitri; J, Julina; H, Herlinda (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Amil Zakat Institution (LAZ) plays a crucial role in collecting and distributing zakat effectively and efficiently. However, in the rapidly developing digital era, LAZ faces new challenges in reaching and involving the younger generation, namely the millennial and Z generations, who have different characteristics and preferences compared to previous generations. This research aims to identify and analyze strategies that can be implemented by LAZ to increase the participation of the younger generation in paying zakat. This research uses qualitative methods and involves 10 muztahik respondents who have the right to pay zakat. The research results show that the use of digital technology, transparency and accountability in zakat management, as well as innovative programs that can attract the interest of the millennial and Z generations, are important keys in LAZ's strategy to attract the younger generation. Challenges faced by LAZ include limited resources, resistance to change, and a lack of in-depth understanding of the preferences and behavior of the millennial and Z generations. This research is expected to provide insight and recommendations for LAZ in formulating more effective and relevant strategies to increase the participation of the younger generation